The Cloud of Unknowing- Singapore Pavilion : 54th International Art Exhibition- La Biennale di Venezia 2011 - Ho Tzu Nyen; Yap, June (Singapore; National Arts Council, 2011)
From June to November 2011, Ho Tzu Nyen represented Singapore at the 54th International Art Exhibition with The Cloud of Unknowing, a film and audio installation titled after a 14th century mystical treatise. 'The Cloud of Unknowing is the first of a new series of works by Ho that reflects his curiosity in the presence and representation of this formless object, in art and art history,' states curator June Yap. This catalogue, made of translucent paper stock with roughed edges, contains four essays, a series of installation photos and screenshots. Ho's other works from 2003 to those forthcoming in 2012 are also briefly documented with images.
English
Keywords: N4390-5098 Visual Arts- Exhibitions; Pavilion catalog; Singapore